Perceptions of Successful Veterinary School Applicants: Assessment Data to Improve Student Success - Whitt, Elizabeth; Walker, Danny; Watson, Diana; Roberts, Jason; Mehlhorn, Joey (Journal of Agricultural Studies, 2021)
Admission to colleges of veterinary medicine has become increasingly more competitive through the years. The increased number of applicants require students and the programs they are attending to help students distinguish themselves in the applicant pool. Many students understand the importance of the science related coursework early on in their undergraduate career. The soft skills along with mentoring have been shown to be important for applicant success. Time management skills can be some of the most vital skills for undergraduate students to practice before matriculation to veterinary school. In addition, group skills and conflict resolution are perceived as important among veterinary alumni and students. Mentoring is critical throughout the education process. The personal aspects and professional guidance given by professors make for the most successful advising of undergraduate pre-veterinary students. Results indicated that students could benefit from communication skills being included throughout the curriculum, especially in context of veterinary science courses.